DOI: 10.22215/etd/2018-13197
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical and Experimental Investigation on Ejector Acoustics and Ejector Silencer Design

Abstract: Ejectors are common devices used across many industries, however, they are often plagued by the presence of low frequency pressure pulsations causing both broadband and tonal noise. This thesis presents a theoretical and experimental investigation into the acoustics of an ejector-silencer combination with the emphasis placed on silencer design. More specifically, the noise generated by the jet, the diffuser and natural modes is explained and estimated. The noise generation mechanisms of impingement tones and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Source: reproduced with permission from Desmarais (2018). 9 increased from 0.7 in small intervals, it is found that the tone grows significantly, with the maximal levels measured somewhere between approximately Mach 0.76 and Mach 0.8. At higher Mach numbers, the amplitude of this tone reduces, resulting in a spectrum which shows no dominant tone.…”
Section: Baseline Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Source: reproduced with permission from Desmarais (2018). 9 increased from 0.7 in small intervals, it is found that the tone grows significantly, with the maximal levels measured somewhere between approximately Mach 0.76 and Mach 0.8. At higher Mach numbers, the amplitude of this tone reduces, resulting in a spectrum which shows no dominant tone.…”
Section: Baseline Resultsmentioning
confidence: 91%
“…Source: reproduced with permission from Desmarais (2018). 9 numbers is attributed to the jet containing more energy at higher Mach numbers, thus being better able to excite the acoustic natural modes of the ejector. As mentioned earlier and detailed in equation 1, the acoustic efficiency of a jet markedly increases with jet velocity.…”
Section: Baseline Resultsmentioning
confidence: 99%
See 3 more Smart Citations